Unrevealing the Impact of Annealing Condition on Catalytic Activity of PtNi Alloy Electrode Towards Oxygen Reduction Reaction - Wardhani, Anindya Pramudya; Tanaya, Salwaa; Pravitasari, Retna Deca; Damisih, Damisih; Arti, Dewi Kusuma; Rahayu, Sri; Gumelar, Muhammad Didik; Fidiani, Elok (Indonesian Journal of Chemistry, 2025)
Alloying platinum (Pt) with transition metals such as nickel (Ni) has been an effective approach for reducing Pt loading and enhancing catalytic activities towards the sluggish oxygen reduction reaction (ORR) on the cathode of proton exchange membrane fuel cell (PEMFC). In this work, we advance the fabrication of PtNi alloy electrodes through direct synthesis on the gas diffusion layer (GDL) utilizing wet chemical reduction methods. The catalytic activities and binding interaction between Pt and Ni are optimized through annealing PtNi electrodes at 200 °C under different gas flows of N2 and the mixture of H2/N2 at 5%/95%. The physical characterization using X-ray diffraction (XRD) analysis and scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX) show the significant effect of the annealing environment on the morphology and distribution of the PtNi alloy catalyst on the GDL surface. The optimized electrodes exhibited enhanced ORR mass activity, with values of 8.17 and 18.26 mA mg−1 for PtNi annealed with N2 and N2/H2, respectively, surpassing the benchmark Pt/C (5.25 mA mg−¹). These results underscore the critical role of the annealing environment in optimizing the catalytic performance of PtNi-based electrodes for PEMFC applications, offering insights into more efficient fuel cell technologies.